Online collaborative work as a learning strategy in virtual environments: an investigation with university students of Infant and Primary Education - Cotán Fernández, Almudena (2021)
This article presents the results of study carried out at a private university in Spain which the main potentialities, benefits and disadvantages of collaborative work at online environments were analyzed. We studied collaborative work as a learning strategy and how it influenced the process of knowledge acquisition of students. Starting from the qualitative method, the structured interview was used as an instrument to collect information. The results of this work analyze how collaborative work influences student learning and what were the most significant organizational modalities, among other aspects. The main conclusions obtained, it is worth highlighting how personal involvement and individual responsibility are essential aspects to generate a good climate of group cohesion.